Implementation of Learning Based on Deep Dialogue Critical Thinking In Citizenship Education Subjects - Rosa Dewi; Noor Maya Sari; Arif Mansyuri (Tarunateach: Journal of Elementary School, 2023)
The implementation of deep dialogue-based critical thinking learning in this study uses descriptive qualitative research methods to find out how the implementation of deep dialogue-based critical thinking learning in civics education subjects in madrasahs is done by collecting interview data and case studies in the field. problems that occur in Madrasah Ibtidaiyah Surabaya City, In the learning process students still have difficulty analyzing and solving problems, especially in Citizenship subjects. During the learning process, students are still passive, very few students dare to answer the problems posed, as well as a lack of students' ability to independently solve problems that require analytical skills with this problem the teacher applies deep dialogue-based learning critical thinking to civic education subjects to increase concentration in gaining knowledge and experience through in-depth dialogue and critical thinking, emphasizing student activity and learning outcomes. on Citizenship education subjects.